2017
DOI: 10.1108/ijbm-08-2016-0111
|View full text |Cite
|
Sign up to set email alerts
|

Quality and image of banking services: a comparative study of conventional and Islamic banks

Abstract: Purpose Bank customers’ perceptions of service quality and service image of Islamic banks may differ from those of conventional banks. The purpose of this paper is to examine the differing perceptions of customers of Islamic and conventional banking systems in an emerging market, which has rarely been addressed and adds to the body of knowledge on this topic. This study also re-examines the SERVQUAL model of customer banking services to measure their impact on customer satisfaction and loyalty. Design/method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 76 publications
7
111
0
11
Order By: Relevance
“…In fact, in a study conducted by Saleh et al (2017) carried out in two Islamic banks, results show that there is a positive effect of perceived quality on the corporate image, pointing to the idea that clients with a higher service quality perception seem to form a more favourable image about the organization. Among others, several studies have been carried out in healthcare contexts, such as Faria and Mendes (2013) in the context of Portuguese healthcare centres, which suggest that perceived service quality seems to have a direct and significant effect on the image of healthcare institutions.…”
Section: Relationship Between Service Quality Organizational Image mentioning
confidence: 99%
“…In fact, in a study conducted by Saleh et al (2017) carried out in two Islamic banks, results show that there is a positive effect of perceived quality on the corporate image, pointing to the idea that clients with a higher service quality perception seem to form a more favourable image about the organization. Among others, several studies have been carried out in healthcare contexts, such as Faria and Mendes (2013) in the context of Portuguese healthcare centres, which suggest that perceived service quality seems to have a direct and significant effect on the image of healthcare institutions.…”
Section: Relationship Between Service Quality Organizational Image mentioning
confidence: 99%
“…Lassar et al (2000) argue that as a critical measure of organizational performance, service quality remains at the forefront of both the marketing literature, and the services marketing literature (Jensen & Markland, 1996;Kant et al, 2017;Sivapalan et al, 2017). Practitioners and academics are keen on accurately measuring service quality in order to better understand its essential antecedents and consequences, and, ultimately, establish methods for improving quality to achieve competitive advantage and build customer loyalty (Palmer & Cole, 1995;Saleh et al, 2017). Service quality is commonly noted as a critical prerequisite for establishing and sustaining satisfying relationships with valued customers.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Parasuraman et al, (1985); Zeithaml and Bitner (1996) has identified that an excellent service quality comprises of five dimensions which are tangibles (appearance of physical facilities such as equipment, personnel and written material), reliability (dependability and accuracy of provided services), responsiveness (staff/personnel willingness to assist customers, provide brisk service and response), assurance (employees knowledge and expertise to ensure trust and confidence to customers) and empathy (customer oriented and compassionate attitude of service provider). The definition and concept of service quality was suggested by and since then it has been widely used by many researchers (Alshurideh, Al-Hawary, Mohammad, Mohammad and Al Kurdi, 2017;Lone and Rehman, 2017;Saleh, Quazi, Keating and Gaur, 2017;Faisal et al, 2016).…”
Section: Service Qualitymentioning
confidence: 99%
“…Carter model is used for examining the service quality and customer perception relationship due to its dual nature (Faisal et al, 2016;Saleh et al, 2017;Parves, 2017). It is considered the most reliable and dependable instrument for the measurement of service quality and customer perception relationship of Islamic bank customers (Othman & Owen, 2001).…”
Section: Measurement Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation